“Review on Forensic Odonto-Stomatology” (Bangladesh Journal of Medical Science, 2021)
Forensic Odontology has become an integral part of forensic medicine over the past decadesthat utilize dental tissue findings to serve the judicial system. Dental tissues remains can be usedfor identification as using them are cost effective, reliable and fast. Forensic odontology is abranch of dentistry that analyzes dental evidence to overlap the dental and legal profession. Thetooth has been used as weapons and under certain circumstances, may leave information aboutthe identity of the biter, age estimation and gender determination. Dentists have a major role toplay in keeping accurate dental records and providing all necessary information so that legalauthorities may recognize mal practice, negligence, fraud or abuse, and identity of unknownindividuals. This paper will try to summarize the various roles of dental experts in forensicmedicine.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.17-23